Enhancement of T cell receptor signaling by a mild oxidative shift in the intracellular thiol Pool - Hehner, Steffen Peter; Schulze-Osthoff, Klaus; Dröge, Wulf (The journal of immunology, 2000)
Exposure of T cells to the macrophage products hydrogen peroxide (HP) or l-lactate (LAC) was previously shown to enhance IL-2 production and to modulate glutathione (GSH) status. We now found that 50 μM HP and 30 mM LAC enhanced strongly the transcription from the IL-2 promoter in Jurkat T cells after stimulation with anti-CD28 together with or without anti-CD3 but not with anti-CD3 Abs alone. Therefore, we used anti-CD3 plus anti-CD28-stimulated cells to investigate the effect of the GSH reductase inhibitor 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) on the signal cascade. BCNU enhanced the transcription to a similar extent as HP or LAC. Lowering the intracellular GSH/GSH disulfide ratio by BCNU, HP, or NO resulted in all cases in the fulminant enhancement of Jun-N-terminal kinase and p38 mitogen-activated protein kinase but not extracellular signal-regulated kinase 1/2. Jun-N-terminal kinase and NF-κB activation was enhanced through pathways involving Rac, Vav1, PKCΘ, p56lck, p59fyn, and IκB kinases. In a cell-free system, the autophosphorylation of rFyn was stimulated by GSH disulfide but not by HP. These findings suggest that the oxidation of the cellular thiol pool may play a role as an amplifying mechanism for TCR/CD3 signals in immune responses.
Gesehen am 03.02.2021